Analisis Pertimbangan Hakim Dalam Menjatuhkan Pidana Penjara Terhadap Anak Pelaku Tindak Pidana Pencurian Dengan Pemberatan Dalam Perspektif Hukum Pidana - Untung Surya Darma; Sri Wahyuni (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Juvenile delinquency is a problem with the social norms that underlie social life or continuity, triggering social tension and posing a threat to social stability. Any individual proven to have committed a crime can legally be punished according to the provisions of applicable laws, including children. Aggravated theft can also be committed by children, one of which is in the case with decision number: 8/Pid.sus-Anak/2022/PN Pdg. The panel of judges sentenced the child to 2 (two) months in prison minus the detention that the child has served. This judge's decision is based on the regulations and spirit of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The limitations of this writing are: 1) What is the form of prison sentence for child perpetrators of crimes from a criminal law perspective? 2) What is the basis for the judge's considerations in sentencing a child perpetrator of aggravated theft in Decision Number 8/Pid.Sus-Anak/2022/PN Pdg from a child protection perspective? To address the issues raised, the author applies a normative legal research method using primary, secondary, and tertiary data. The research concludes that in the Indonesian criminal law system, provisions regarding the imposition of criminal penalties are stipulated in the Criminal Code (KUHP) for general crimes, while specific crimes are regulated in laws related to the type of crime. More specifically, provisions regarding the detention of children who commit crimes are regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The basis for the judge's considerations in imposing criminal penalties on children as perpetrators of aggravated theft, particularly in Decision Number: 8/Pid.Sus-Anak/2022/PN Pdg, of course, the judge uses these considerations to ensure that the decision is deemed appropriate and fair.